2010
DOI: 10.1177/030089161009600518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microRNA-206 on Cytoskeleton Remodelling by Downregulating Cdc42 in MDA-MB-231 Cells

Abstract: The results suggest that miR-206 may suppress invasion and migration of MDA-MB-231 cells in vitro partly via regulating actin cytoskeleton remodelling such as filopodia formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…The expression of mir206 is dramatically reduced in an ALS mouse model, and deficiency of mir206 in this ALS mouse model accelerates disease progression (68). mir206 also inhibits cancer cell proliferation, invasion, and metastasis by acting as a tumor suppressor (35,51,54,65,69). mir206 is one of the earliest expressed miRNAs during zebrafish development (8,67), but its role in embryonic development is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of mir206 is dramatically reduced in an ALS mouse model, and deficiency of mir206 in this ALS mouse model accelerates disease progression (68). mir206 also inhibits cancer cell proliferation, invasion, and metastasis by acting as a tumor suppressor (35,51,54,65,69). mir206 is one of the earliest expressed miRNAs during zebrafish development (8,67), but its role in embryonic development is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, two other microRNAs have been shown to indirectly regulate MMP-2 and MMP-9 expression. 48,49 First, miR-206 was found to downregulate MMP-2 and MMP-9 expression at the protein level and inhibit the invasion and migration of MDA-MB-231 cells in vitro. 48 In addition, Wu et al found that miR-340 directly targeted the c-Met gene and consequently inhibited MMP-2 and MMP-9 expression, thereby suppressing tumor cell migration and invasion.…”
Section: Microrna-mediated Regulation Of Archetypal Mmpsmentioning
confidence: 99%
“…48,49 First, miR-206 was found to downregulate MMP-2 and MMP-9 expression at the protein level and inhibit the invasion and migration of MDA-MB-231 cells in vitro. 48 In addition, Wu et al found that miR-340 directly targeted the c-Met gene and consequently inhibited MMP-2 and MMP-9 expression, thereby suppressing tumor cell migration and invasion. 49 In addition, miR-9 and miR-196b were shown to regulate gelatinase expression in uveal melanoma 50 and gastric cancer, 51 respectively.…”
Section: Microrna-mediated Regulation Of Archetypal Mmpsmentioning
confidence: 99%
“…Liu and his colleagues have found that miR-137 may have a tumor suppressor function by directly targeting Cdc42 to inhibit the proliferation and invasion activities of colorectal cancer cells [49,50]. MiR-206 may suppress invasion and migration of MDA-MB-231 cells in vitro partly via regulating actin cytoskeleton remodelling by downregulating Cdc42 [51]. MiR-29 activates p53 by targeting p85 alpha and Cdc42 [52].…”
Section: Rho Family Of Gtpasesmentioning
confidence: 99%